Essential oils as capsule disruptors: enhancing antibiotic efficacy against multidrug-resistant Klebsiella pneumoniae - El-Demerdash, Azza SalahEldin; Alfaraj, Rihaf; Farid, Faten A.; Yassin, Mohamed H.; Saleh, Abdulrahman M.; Dawwam, Ghada E. (Frontiers in Microbiology, 2024)
Background Multidrug-resistant Klebsiella pneumoniae (MDR-KP) poses a significant global health threat due to its involvement in severe infections and high mortality rates. The emergence of MDR strains necessitates the exploration of alternative therapeutic strategies. Methods K. pneumoniae isolates were obtained from human and animal sources. Antibacterial susceptibility testing was performed, followed by the evaluation of essential oil activity through inhibition zone, MIC, and MBC determinations. Checkerboard assays were conducted to assess synergistic effects with amikacin. Gene expression analysis and transmission electron microscopy were employed to elucidate the mechanisms of action. Molecular docking studies were performed to identify potential binding targets of bioactive compounds. Results Klebsiella pneumoniae was isolated from 25 of the100 samples examined, representing a prevalence rate of 25%. All isolates were found to be multidrug-resistant. Tea tree and thyme essential oils exhibited potent antibacterial activity and synergistic effects with amikacin. Notably, these combinations significantly downregulated the expression of key capsule virulence genes (wcaG, rmpA, magA, uge, and wabG), suggesting a novel mechanism for enhancing amikacin efficacy. Transmission electron microscopy revealed disrupted cell integrity in MDR-KP cells treated with the combinations. Molecular docking analysis identified Terpinen-4-ol, Farnesol, 1,4-Dihydroxy-p-menth-2-ene, and 7-Oxabicyclo [4.1.0] heptane as potential bioactive compounds responsible for the observed effects. Conclusion By effectively combating MDR-KP, this research holds promise for reducing antibiotic resistance, improving treatment outcomes, and ultimately enhancing potential care.